A Review on Hematopoietic Stem Cell Treatment for Epilepsy - Ghanta, Mohan K.; Merchant, Neha; Bhaskar, Lakkakula V.K.S. (CNS & Neurological Disorders - Drug Targets, 2021)
Epilepsy responds to pharmacotherapy in its initial stages. The response of some forms of epilepsy, like the refractory epilepsy, is extremely low. Surgical management of epilepsy is associated with complications, which necessitates the search for novel and modern strategies for the treatment of epilepsy. Neuroprotection and neuronal regeneration are the major targets that must be accomplished by the new strategies. Hematopoietic Stem Cell (HSCs) therapy for epilepsy has shown promising results in pre-clinical studies with marginal clinical effects. This review explores the characteristics, mechanism of action, and clinical significance of HSCs therapy for the treatment of epilepsy.
Keywords: neuronal regeneration